An annotated bibliography of the history of medicine and health in Australia - Gandevia, Bryan, 1925- (Royal Australasian College of Physicians, 1984)
Selected multidisciplinary references of significant interest in an Australian context to social or medical historians; all items relate directly to the history of medicine. Includes some citations to mid-1983. Classified arrangement. Entries give bibliographical information and brief annotations. Contains a list of journals with abbreviations. Author and subject indexes.